Hypercholesterolemia Inhibits Endothelial Cell Healing After Arterial Injury Though Reactive Oxygen Species - Rosenbaum, Michael A. (2011)
OBJECTIVE: Endothelial cell (EC) migration is essential for arterial healing after angioplasty. Oxidized low-density lipoproteins and oxidative stress decrease EC migration in vitro. The objective of this study was to determine the effect of hypercholesterolemia and oxidative stress on EC healing after an arterial injury. METHODS AND RESULTS: C57Bl/6 wild-type mice were placed in one of eight groups: chow diet (n = 11), high cholesterol (HC) diet (n = 11), chow diet plus paraquat (n = 11), HC diet plus paraquat (n = 11), chow diet plus N-acetylcysteine (NAC) (n = 11), HC diet plus NAC (n = 11), chow diet plus paraquat and NAC (n = 11), and HC diet plus paraquat and NAC (n = 11)After two weeks on the assigned diet with or without NAC, the carotid artery was injured using electrocautery. Animals in the paraquat groups were given 1 mg/kg intraperitoneally to increase oxidative stress. After 120 hours, Evans Blue dye was infused intravenously to stain the area of the artery that remained deendothelialized. This was used to calculate the percentage of reendothelialization. Plasma and tissue samples were analyzed for measures of oxidative stress. The HC diet increased oxidative stress and reduced EC healing compared with a chow diet, with EC covering 26.8 ± 2.8% and 48.1 ± 5.2% (P < .001) of the injured area, respectively. Administration of paraquat decreased healing in both chow and HC animals to 18.1 ± 3.5% (P < .001) and 9.8% ± 4.6% (P < .001), respectively. Pretreatment with NAC (120 mmol/L in drinking water) for 2 weeks prior to injury, to decrease oxidative stress, improved EC healing to 39.9 ± 5.7% (P < .001) in hypercholesterolemic mice and to 30.7 ± 3.6% (P < .001) in the paraquat group. NAC treatment improved healing to 24.6% ± 3.4% (P < .001) in hypercholesterolemic mice treated with paraquat. CONCLUSION: Reendothelialization of arterial injuries is reduced in hypercholesterolemic mice, and is inversely correlated with oxidative stress. An oral antioxidant decreases oxidative stress and improves EC healing. CLINICAL RELEVANCE: Vascular injury following cardiovascular intervention including cardiac and peripheral arterial angioplasty and stenting is associated with inflammation and oxidative stress. Hypercholesterolemia is also associated with increased oxidative stress. Oxidative stress, regardless of the source, induces cellular dysfunction in endothelial and smooth muscle cells that reduces healing after arterial injury. Decreasing oxidative stress with an exogenously administered antioxidant can improve endothelial cell healing, and this is important to control intimal hyperplasia and reduce the thrombogenicity of the vessel.